(untitled) (International Journal of Engineering and Computer Science, 2014)
Requirements elicitation is the process of seeking, uncovering, acquiring, and elaborating requirements for computer based systems. It is generally understood that requirements are elicited rather than just captured or collected. This implies there are discovery, emergence, and development elements to the elicitation process. Requirements elicitation is a complex process involving many activities with a variety of available techniques, approaches, and tools for performing them. The relative strengths and weaknesses of these determine when each is appropriate depending on the context and situation. One of the most important aspects of developing a large Web-based project is getting the correct requirements from the client. Time and money can be lost if the requirements are incomplete or inaccurate. Traditional Web design sources tend to gloss over this important activity. Requirement elicitation is a critical activity in the requirement development process and it explores the requirements of stakeholders. The success or failure of this process is based on identifying the relevant stakeholders and discovering their needs as well as the quality of requirements. The quality of the requirements is greatly influenced by methods applied during requirements elicitation process. Only complete and structured requirements make these projects more reliable. The common challenges that analysts face during elicitation process are to ensure effective communication between stakeholders as well as the acquisition of tacit knowledge. Mostly errors in the systems are due to poor communication between user and analyst, and these errors require more resources (time and money) to correct them. The understandability problems during elicitation process of large web projects can lead to requirements ambiguous, inconsistent, incorrect and unusable. Different methods (Conversational, Observational, Analytical and Synthetic) are available to deal with the problems during requirement elicitation process. The challenge for analysts is to select an appropriate method or set of methods and apply them for the clear, consistent and correct requirement gathering. This study based on the results of interviews conducted to the professionals, who have industrial experience in development of web systems. The elicitation problems that are identified in literature and interview along with applicability of elicitation methods for requirement gathering in large web projects development are documented in this report. Software engineering is a mature field that can help in the quest for more complete and accurate requirement gathering. The objectives of this chapter are to present a comprehensive survey of important aspects of the techniques, approaches, and tools for requirements elicitation, and examine the current issues, trends, and challenges faced by researchers and practitioners in this field.